Peningkatan Keterampilan Komunikasi Matematika pada Pokok Bahasan Segiempat dan Segitiga dengan Model Problem Based Learning(PTK Pembelajaran Matematika Kelas VII C SMP Negeri III Boyolali) - Ningtyas, Dinda Praoktavia (2015)
The purpose of this research is to improve mathematics communication skills on the subject of square and triangle using Problem Based Learning Model is conducted in SMP N III Boyolali Class VII C. The type of this research is a Classroom Action Research (CAR). Students of class VII C as the recipient of the action while the mathematics teacher as a giver of the action. The method used to collect data through observation, field notes, documentation, testing and interview. The data analysis techniques used are data collection process, data presentation, and data verification. The results showed an increase in communication skills that can be viewed from 1) the students who brave to ask a question only 16,67% increase to 55,56%; 2) the students are able to propose the ideas only 25% increase to 55,56%; 3) the students are able to work in a group only 25% increase to 63,88%; 4) the students are able to present the work of the group only 25% increase to 55,56%; 5) the students are able to do mathematics questions given by the teacher only 25% increase to 58,33%. It can be concluded that the learning model Problem Based Learning can improve the mathematic communication skills of the students. Keywords: Problem Based Learning